Improving Maternal Health Literacy Through Educational Intervention On Pregnancy Danger Signs: A Pre-Post Study In Batam, Indonesia: Peningkatan Literasi Kesehatan Ibu Hamil Melalui Intervensi Edukasi Tentang Tanda Bahaya Kehamilan: Studi Pre-Post Di Batam, Indonesia - Prihadianto, Dino Gagah; Astiah, Andi Asda; Romiana, Dwi (Bhakti Sabha Nusantara, 2025)
Background: Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in Indonesia remain high and pose significant challenges in achieving the Sustainable Development Goals (SDGs) 2030. One of the contributing factors is the low awareness among pregnant women regarding the danger signs of pregnancy. This community service activity aimed to improve maternal health literacy through structured education on pregnancy danger signs at Tridi Clinic, Batam. Methods: The intervention involved 60 pregnant women and employed pre-test and post-test assessments, lectures, group discussions, demonstrations, and the distribution of educational materials. Data were analyzed using descriptive statistics and the percentage increase in knowledge. Results: A significant improvement was observed in participants’ knowledge, with scores increasing from 52.3% in the pre-test to 83.7% in the post-test. The educational methods used proved effective, supported by participants’ motivation, health facility support, and the competence of the facilitator team. Conclusion: Structured education on pregnancy danger signs effectively enhances pregnant women's knowledge. Similar programs should be replicated regularly to support efforts in reducing maternal and infant mortality in Indonesia.